PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS PENEMUAN TERBIMBING UNTUK MENINGKATKAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMP - Yerizon Yerizon; Widya Novita Sari (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2022)
This research is motivated by the low ability of student’s mathematical communication and the instructional package used has not provided opportunities for students to construct student’s creative ideas in understanding concepts and discovering principles. This research aims to obtain a guided discovery-based mathematics instructional package to improve mathematical communication of VIII grade junior high school students that is valid and practical. The instructional package developed is the lesson plans and student worksheets. This type of research is research and development. The development model used in this research is the Plomp model, which consists of 3 phases, namely the preliminary research phase, the development or prototyping phase, and the assessment phase. In the preliminary research phase, the analysis required for the development of guided discovery-based instructional package was carried out. In the development or prototyping phase, the design of guided discovery-based mathematics instructional package was carried out by paying attention to aspects of the feasibility of content and presentation, language, and graphics. In the development or prototyping, formative evaluation was carried out, namely self-evaluation, one-to-one evaluation, and small group evaluation. In the assessment phase, it was carried out by giving a practicality test questionnaire based on guided discovery to mathematics teachers and VIII grade students. The test subjects in this study were students of VIII.2 grade of SMPN 12 Padang in the academic year 2020/2021. The instruments used in the preliminary research phase were observation sheets, interview guides with teachers, and student questionnaires. The validity instruments were the self-evaluation sheet and the lesson plans and student worksheets validation sheet. The practical instruments were observation sheets of lesson plans, teacher response questionnaires, and student response questionnaires. The results of the analysis of the data from the lesson plans and student worksheets validation sheets show that the guided discovery-based mathematics instructional package developed is valid in terms of content and presentation, language, and graphics according to the expert judgment. Guided discovery-based mathematics instructional package are practical in terms of ease of use and time. This was obtained based on the results of observations of the implementation of the lesson plans, teacher response questionnaires, and student response questionnaires.